Alkali earth MOx (x = 6, 7, 9, 12) polyhedra tuned cadmium selenites with different dimensions and diverse SeO32− coordinations. Issue 44 (27th October 2017) - Jia, Ying-Jie; Chen, Yi-Gang; Yao, Xiao-Ni; Zhang, Xian-Ming
Abstract : Alkali earth cation-tuned framework of cadmium selenites resulting in evolvement of the structures from high dimension to low dimension. Abstract : A series of alkali earth cadmium selenites including MgCd3 (SeO3 )4 (1 ), Ca0.7 Cd2.3 (SeO3 )3 (2 ), SrCd(SeO3 )2 (3 ) and BaCd(SeO3 )2 (4 ) are synthesized by hydrothermal reaction and studied in detail by single crystal and powdered X-ray diffractions, thermal analyses, IR and UV spectral measurements and dipole moment calculation.1 features a 3D anionic [Cd3 (SeO3 )4 ] 2− framework constructed from isolated SeO3 trigonal pyramids and 2D [Cd3 O12 ] n layers, in which the [Cd3 O12 ] n layer is composed of edge-shared [Cd2 O10 ] 16− dimers and butterfly-like [Cd4 O20 ] 32− tetramers.2 shows a smooth 2D [Cd2 (SeO3 )3 ] n layer composed of unique [Cd(SeO3 )] n double chains.3 exhibits a wavelike 2D [Cd(SeO3 )2 ] n layer constructed from corner-shared CdO6 octahedra and isolated SeO3 trigonal pyramids.4 displays a windmill-like 1D [Cd(SeO3 )2 ] n chain built from zigzag [CdO4 ] n chain motifs and isolated SeO3 trigonal pyramids. The alkali earth oxide motifs demonstrate interesting and regular changes from isolated MgO6 octahedra, CaO7 polyhedra, and SrO9 tri-capped trigonal prisms based on a ribbon chain to BaO12 icosahedra based on a brucite-like layer, and meanwhile the SeO3 groups are observed from variable tetradentate to hexadentate coordination modes. These flexible motifs reveal that cadmium selenites are strongly affected by the size of the alkali earth cations, providing a feasible approach to modulating their space structure via selection of template cation.